Response of cocoa pod borer to chlorogenic acid. Issue 1 (April 2020) - Firmansyah, A P; Sjam, S; Alam, G; Dewi, V S
Abstract: Chlorogenic acid was first isolated from coffee beans, and this compound is found in many plants including cocoa fruit. Besides functioning as an antibacterial and antioxidant, this compounds act as insect repellents and attractants. According the literature, chlorogenic acid is a stimulant for laying eggs. Because this compound is also found in cocoa and has a function in attracting insects, an experiment was conducted to see the response of the main cocoa pests, cocoa fruit borer (CPB). Pure dissolved chlorogenic acid was divided into several concentrations and then tested with CPB adults male and female. The results of this test show that at concentrations of 5% of chlorogenic acid compounds attract more CPB, and the average of the CPB adults whose choose is female. The most of CPB visit time was 3 hours after the experiment was carried out then stop visit after 18 hours.